A study of micro structural, magnetic and electrical properties of La-Co-Sm nanoferrites (LCSF) synthesized by sol-gel method - Kadhum Jassem Wadi; Hayder Abdulameer Abbas; Adnan Hussein Ali; Ban Mohammed Hasan (International Journal of Electrical and Computer Engineering (IJECE), 2020)
A Lanthanum (La3+) doped Samarium-Cobalt nanoferrites (La_x,Co_0.2,Sm_0.2,Fe_(2-x) O_4, where x=0.0,0.5,1.0) have been synthesized by sol-gel method in citrate media. Obtained spinal ferrites micro structure properties have been investigated by XRD, FTIR, SEM-EDX, and TEM-SAED techniques. All the samples are nano in size with significant hysteresis. Micro structural analysis by XRD confirms the obtained samples showing the single phase cubic spinal structures with an average crystal size found from 12 nm to 25 nm, while the average particles sizes identified from TEM analysis are ranging from 21.5nm-26.8 nm (~23.4nm) and from 20.5 nm to 28(~26.4nm) nm for x=0.5,1.0. The lattice parameter found to be a= 8.402, 8.423, 8.467Å for the respective values of x= 0.0, 0.05, and 1.0. Electrical properties show increase in dc resistivity with increase in La3+ ion concentration. Finally, it was concluded that the doping of Lanthanum ion (La3+) in the ferrites structure is found to influencing the structural and electrical properties without scarifying the ferromagnetic character.